Proportion and factors associated obstructive sleep apnoea (OSA) risk among adults in Sepang: a cross-sectional study - Khamis, Siti Nur Faezah (Faculty Of Medicine Universiti Putra Malaysia, 2023)
Sleep is often viewed by the general public as a “perceptual hole in time” where it is the period in which nothing productive occurs. However, sleep is an important part of health which affects mental and physical health. Sleep-disordered breathing (SDB) encompasses a range of respiratory disorders that are distinguished by intermittent pauses in breathing during the sleep cycle. This includes obstructive sleep apnoea (OSA), a global disease with a rising incidence along with its comorbidity. OSA creates an impact on the quality of life as it is associated with multiple negative implications which include neurocognitive problems and increases the risk of cardiometabolic diseases. This article illustrates the importance to determine the proportion of patients in the district of Sepang who are at high risk of obstructive sleep apnoea (OSA) and its determinants. Method: A cross-sectional study was carried out among individuals aged 18 years and above in Sepang district Malaysia. Using systematic random sampling, 521 participants were recruited. The questionnaire given gathered respondents information regarding their socio-demography, clinical profiles, and the STOP-BANG questionnaire was used to screen for OSA. Result: Almost a third of the participants (30.3%) were at risk of having OSA. It is found that the predictors for having OSA are menopausal women (AOR: 2.46; 95% CI: 1.22, 4.93; p = 0.011) and having large waist circumference measurement (AOR: 1.07; 95% CI: 1.04,1.10; p <0.001). Conclusion: The findings in this study will help healthcare workers to detect early patients at risk of OSA with the aid of STOP-BANG questionnaire.